The effect of different drying times on physicochemical characteristics of surimi powder from kurisi (Nemipterus japonicus) - Hidayatun Muyasyaroh; Asep Awaludin Prihanto; Wenny Bekti Sunarharum (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Surimi powder is a modification product of frozen surimi blocks produced through drying at a specific temperature and time. Surimi powder has many uses in the diversification of processed fishery products, namely to increase the nutritional and functional value of a product, especially cereal products. This research aims to determine the effect of different drying times on the physicochemical characteristics of the surimi powder of kurisi fish (Nemipterus japonicus). The drying times were 9, 12, and 15 hours at 60oC. The resulting kurisi fish surimi powder was observed for its characteristics, including proximate values, color, and product acceptance and then analyzed using Minitab software version 19. The results analysis of variance showed that the drying time had a significant effect (p < 0.05) on the value of water content, protein content and ash content, brightness (L*), and yellowish color (b*) but had no significant effect (p > 0.05) on the values of a* and ΔE*ab.